2021
DOI: 10.3389/fimmu.2021.633297
|View full text |Cite|
|
Sign up to set email alerts
|

CXCL17 Is a Specific Diagnostic Biomarker for Severe Pandemic Influenza A(H1N1) That Predicts Poor Clinical Outcome

Abstract: The C-X-C motif chemokine ligand 17 (CXCL17) is chemotactic for myeloid cells, exhibits bactericidal activity, and exerts anti-viral functions. This chemokine is constitutively expressed in the respiratory tract, suggesting a role in lung defenses. However, little is known about the participation of CXCL17 against relevant respiratory pathogens in humans. Here, we evaluated the serum levels and lung tissue expression pattern of CXCL17 in a cohort of patients with severe pandemic influenza A(H1N1) from Mexico C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…In vivo , endogenous CXCR4 inhibitors may represent an important regulatory mechanism to prevent excessive receptor activation. Notably CXCL17 expression can reach ~ 60 ng/ml in vitro while serum CXCL17 concentrations can reach ~ 5 ng/ml during influenza infection 10 . Since CXCL17 expression is highly localised to secretory cells in mucosal tissue 39 it is plausible that CXCL17 expression reaches concentrations sufficient to inhibit CXCR4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo , endogenous CXCR4 inhibitors may represent an important regulatory mechanism to prevent excessive receptor activation. Notably CXCL17 expression can reach ~ 60 ng/ml in vitro while serum CXCL17 concentrations can reach ~ 5 ng/ml during influenza infection 10 . Since CXCL17 expression is highly localised to secretory cells in mucosal tissue 39 it is plausible that CXCL17 expression reaches concentrations sufficient to inhibit CXCR4.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CXCL17 has antimicrobial properties at high concentrations 5 and modulates angiogenesis 4,6 . CXCL17 has also been implicated in several pathologies including breast 7 and hepatocellular cancers 8 , as well as inflammatory lung pathologies such as idiopathic pulmonary fibrosis 5 , asthma 9 , influenza 10 and SARS-CoV-2 11 infection. Despite mediating a wide range of important functional responses, the receptor(s) for CXCL17 are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…We recruited 31 consecutive individuals with severe pandemic influenza A(H1N1) from a previously reported cohort (Choreño-Parra and others 2021c , 2021d ). Patients attending with acute respiratory distress syndrome (ARDS), who required intensive care unit admission and mechanical ventilation (MV), were eligible for this study if they provided adequate samples for analysis and met the inclusion criteria described before (Choreño-Parra and others 2021c , 2021d ). Data and specimens from a comparative cohort of age- and sex-matched HC ( n = 8) and patients with severe COVID-19 ( n = 16) were also included in the following analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, investigations of CXCL17 serum levels in patients with influenza A (H1N1) found that elevated CXCL17 levels were associated with a bad prognosis, leading to kidney damage and death. After in vitro infection with the influenza A (H1N1) pdm09 virus, human alveolar A549 cells and peripheral blood monocyte‐derived macrophages are thought to generate CXCL17 (Choreño‐Parra, Jiménez‐Álvarez, et al, 2021). Due to the convergence of influenza and COVID‐19, which is expected to be one of the most serious public health crises in recent history, these data might aid clinical decision‐making during the flu season.…”
Section: Cxcl17 As a Biomarker In Nonmalignant Diseasesmentioning
confidence: 99%